2013
DOI: 10.19154/njwls.v3i3.3018
|View full text |Cite
|
Sign up to set email alerts
|

Habituating pain: Questioning pain and physical strain as inextricable conditions in the construction industry

Abstract: In this article, we investigate the relations between discursive practices within the Danish construction industry and the perceived pain, physical deterioration, and strain affecting the construction workers. Of central importance is the widely accepted hegemonic discourse on physical strain and pain as unavoidable conditions in construction work. Based on 32 semi-structured interviews performed in eight case studies within four different construction professions, workers’ descriptions of physical strain and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 32 publications
4
45
0
2
Order By: Relevance
“…Furthermore, Gherardi and Nicolini [7] and Paap [8] have in their sociological and ethnographic studies identified a tendency among both construction workers and employers to individualize blame for ‘risky behaviour’ rather than emphasizing organizational or collective bases for accidents. This view is confirmed by other studies showing that construction workers often share the common belief that they individually through their work practices are the main agents of exposing themselves to risk factors for developing pain, as they choose to lift heavy loads, work fast and hard and to disregard health recommendations [10]. …”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…Furthermore, Gherardi and Nicolini [7] and Paap [8] have in their sociological and ethnographic studies identified a tendency among both construction workers and employers to individualize blame for ‘risky behaviour’ rather than emphasizing organizational or collective bases for accidents. This view is confirmed by other studies showing that construction workers often share the common belief that they individually through their work practices are the main agents of exposing themselves to risk factors for developing pain, as they choose to lift heavy loads, work fast and hard and to disregard health recommendations [10]. …”
Section: Introductionsupporting
confidence: 55%
“…Based on studies in different Western construction industries, scholars such as Applebaum [6], Gherardi and Nicolini [7], Paap [8], Thiel [9] and Ajslev et al [10] all found that strength, endurance and self-reliance are perceived as positive identity signifiers. Indeed, there is a general agreement that these characteristics are of central importance for maintaining hierarchical positioning in the professional work gang, which is a central unit of organization in most construction work.…”
Section: Introductionmentioning
confidence: 99%
“…Such expectations are evident across multiple studies of male dominated occupational contexts including construction (Ajslev et al, 2013), professional sports (Hammond et al, 2013;Roderick, 2006), and mining (Wicks, 2002). In fact, playing through pain and injuries is viewed as a normal part of an athlete's "job" (Hammond et al, 2013).…”
Section: Acceptance and Normalization Of Work Injuries And Painmentioning
confidence: 99%
“…Men's bodies may also be viewed as "corporeal capital" and strategies are frequently employed by managers and coaches to discredit the severity of injuries in order to encourage injured professional athletes to return to play/work (Roderick, 2006). Similarly, within the construction industry, Ajslev, Lund, and Møller describe how established working class masculinities-which typically emphasizes strength, stamina and the ability to withstand physical pain-in combination with increased time and productivity pressures, increase the prevalence of musculoskeletal occupational injuries amongst men (Ajslev et al, 2013).…”
Section: Acceptance and Normalization Of Work Injuries And Painmentioning
confidence: 99%
“…Studies suggest that both structural and cultural changes are necessary to create changes in the construction industry [44,51]. The lack of effect from the intervention in the present study may be related to the culture in the construction industry where WMSD is an accepted part of being a construction worker [52,53].…”
Section: Discussionmentioning
confidence: 59%